Adjuncts to blood component therapies for the treatment of bleeding in the intensive care unit - Levy, Jerrold H. (Transfus Med Rev, 2017)
Patients who are critically ill following surgical or traumatic injury often present with coagulopathy as a component of the complex multi-system dysfunction that clinicians must rapidly diagnose and treat in the intensive care environment. Failure to recognize coagulopathy while volume resuscitation with crystalloid or colloid takes place, or an unbalanced transfusion strategy focused on packed red blood cell transfusion, can all significantly worsen coagulopathy leading to increased transfusion requirements and poor outcomes. Even an optimized transfusion strategy directed at correcting coagulopathy and maintaining clotting factor levels carries the risk of a number of transfusion reactions including transfusion related acute lung injury, transfusion related circulatory overload, anaphylaxis, and septic shock. A number of adjunctive strategies can be employed either to augment a balanced transfusion approach or as alternatives to blood component therapy. Coupled with an appropriate and timely laboratory testing, this approach can quickly diagnose a patient’s specific coagulopathy and work to correct it as quickly as possible, minimizing the requirement of blood transfusion and the pathophysiologic effects of excessive bleeding and fibrinolysis. We will review the literature supporting this approach and provide insight into how these approaches can be best utilized to care for bleeding patients in the ICU. Finally, the increasing use of several novel oral anticoagulants (NOACs), novel anti-platelet drugs, and low molecular weight heparin to clinical practice has complicated the care of the coagulopathic patient when these drugs are involved. Many clinicians familiar with heparin and warfarin reversal are not familiar with the optimal way to reverse the action of these new drugs. Patients treated with these drugs for a wide variety of conditions including atrial fibrillation, stroke, coronary artery stent, deep venous thrombosis, and pulmonary embolism will present for emergency surgery and will require management of pharmacologically induced post-operative coagulopathy. We will discuss optimized strategies for reversal of these agents and strategies that are currently under development.